Physical activity reduces internet addiction among “post-00” college students: The mediating role of coping styles - Cheng, Meichao; Wang, Shun; Wang, Ya; Zhang, Rong; Qin, Likai (Frontiers in Psychology, 2023)
Objective To explore the role of coping styles (CS) in mediating the relationship between physical activity (PA) and internet addiction (IA), and to provide a theoretical basis for the prevention and treatment of IA among Chinese “post-00” college students. Methods A total of 410 university students from five universities in Anhui Province were surveyed using the Chinese Internet addiction scale, the Coping Styles Scale for Chinese University Students, and the International Physical Activity Scale Short Form. Results (1) Boys are better than girls in PA. However, there was no significant difference between male and female students on CS and IA. (2) PA was positively correlated with CS (r = 0.278, p < 0.01), PA was negatively correlated with IA (r = −0.236, p < 0.01), CS was negatively correlated with IA (r = −0.560, p < 0.01). (3) PA was negatively predicted IA (B = −0.198, p < 0.01), PA was positively predicted CS (B = 0.986, p < 0.01), CS was negatively predicted IA (B = −0.065, p < 0.01). (4) CS plays a partially mediating role between PA and IA, with a mediating effect proportion of 48.33%. Conclusion PA can improve IA not only directly for university students, but also indirectly by increasing CS. The intervention for IA of “post-00” college students can start by increasing PA and improving CS.